Nonfullerene Electron Transporting Material Based on Naphthalene Diimide Small Molecule for Highly Stable Perovskite Solar Cells with Efficiency Exceeding 20% - Jung, Su Kyo; Heo, Jin Hyuck; Lee, Dae Woon; Lee, Seung Chul; Lee, Seung Heon; Yoon, Woojin; Yun, Hoseop; Im, Sang Hyuk; Kim, Jong H.; Kwon, O. Pil (Advanced Functional Materials, 2018)
This study reports a new nonfullerene electron transporting material (ETM) based on naphthalene diimide (NDI) small molecules for use in high-performance perovskite solar cells (PSCs). These solar cells simultaneously achieve high power conversion efficiency (PCE) of over 20% and long-term stability. New NDI-ID (N,N′-Bis(1-indanyl)naphthalene-1,4,5,8-tetracarboxylic diimide) consisting of an N-substituted indane group having simultaneous alicyclic and aromatic characteristics is synthesized by a low-cost, one-step reaction, and facile purification method. The partially flexible characteristics of an alicyclic cyclopentene group on indane groups open the possibility of low-temperature solution processing. The conformational rigidity and aromaticity of phenyl and alicyclic groups contribute to high temporal stability by strong secondary bonds. NDI-ID has herringbone packed semiconducting NDI cores that exhibit up to 0.2 cm2 V−1 s−1 electron mobility in field effect transistors. The inverted PSCs based on CH(NH2)2PbI3– xBrx with NDI-ID ETM exhibit very high PCEs of up to 20.2%, which is better than that of widely used PCBM (phenyl-C61-butyric acid methyl ester) ETM-based PSCs. Moreover, NDI-ID-based PSCs exhibit very high long-term temporal stability, retaining 90% of the initial PCE after 500 h at 100 °C with 1 sun illumination without encapsulation. Therefore, NDI-ID is a promising ETM for highly efficient, stable PSCs.
Keywords: Conformational rigidity; Electron transporting materials; Flexible characteristics; High power conversion; High temporal stability; Low temperature solutions; Naphthalene diimide; Purification method; electron transporting materials; naphthalene diimide; perovskite solar cells